Host language learning and sense of belonging: the perspective of migrant students - Queirós, Maria Luís; Duarte, Isabel Margarida; Ferreira, Pedro (Frontiers in Education, 2025)
IntroductionIn this article, we explore the role of the host language, and of civic participation, in the integration and inclusion of adult migrants and refugees in the Northern region of Portugal. To do so, we set the research question “What is the role of the host language, its learning and its use in the integration and inclusion of adult migrants and refugees in Portugal?”. This study draws on the works of Ager and Strang, Narli and Özaşçılar, O'Reilly and Silver to explain the establishment process that adult migrants and refugees go through in the host society, and is guided by the perspective that host language is not merely a communicative tool, playing a transformative role, enabling learners to move from passive positions to active, agentive ones. As sense of community plays a role in this process, we mobilize the model proposed by McMillan and Chavis.MethodsWe conducted an extensive qualitative study on the perspectives of adult migrants learning Portuguese as host language students in public schools and social organizations which included 20 semi-structured interviews.Results and discussionOur main results show the host language as facilitating these students' sense of belonging in the host society, boosting, on the one hand, their autonomy and self-confidence, which contributes to their empowerment, and individual agency; and on the other hand, the ongoing development of social relations and networks that counter isolation, exclusion, and marginalization.